Biphenyls in Clusiaceae: Isolation, structure diversity, synthesis and bioactivity - Wang, Youyi; Huang, Qing; Zhang, Li; Zheng, Changwu; Xu, Hongxi (Frontiers in Chemistry, 2022)
Clusiaceae plants contain a wide range of biologically active metabolites that have gotten a lot of interest in recent decades. The chemical compositions of these plants have been demonstrated to have positive effects on a variety of ailments. The species has been studied for over 70 years, and many bioactive compounds with antioxidant, anti-proliferative, and anti-inflammatory properties have been identified, including xanthones, polycyclic polyprenylated acylphloroglucinols (PPAPs), benzophenones, and biphenyls. Prenylated side chains have been discovered in many of these bioactive substances. To date, there have been numerous studies on PPAPs and xanthones, while no comprehensive review article on biphenyls from Clusiaceae has been published. The unique chemical architectures and growing biological importance of biphenyl compounds have triggered a flurry of research and interest in their isolation, biological evaluation, and mechanistic studies. In particular, the FDA-approved drugs such as sonidegib, tazemetostat, daclatasvir, sacubitril and trifarotene are closely related to their biphenyl-containing moiety. In this review, we summarize the progress and development in the chemistry and biological activity of biphenyls in Clusiaceae, providing an in-depth discussion of their structural diversity and medicinal potential. We also present a preliminary discussion of the biological effects with or without prenyl groups on the biphenyls.